An experimental study of the structural capacity of rectangular concrete beam with rice husk concrete (RHC) under flexural test- 5% and 15% rice husk replacement - Muhammad Adib Azri, Mohamad Nasaruddin (2019)
The purpose of this study is to investigate the ultimate loading capacity, maximum moment capacity and deflection that can withstand by a reinforced concrete with the replacement of certain percentage of fine aggregate or sand with raw rice husk. The percentage replacements of the raw rice husks involve in this study are 5% and 15% mixed with concrete grade C25/30. The total of sample that had been prepared is 9 reinforced concrete beams with dimensions of 1500mm x 150mm x 300mm for flexural test and 9 cube samples which dimension size is 150mm x 150mm x 150mm for compressive strength test. Within the 9 beam samples, 3 of it is for controlled sample as references and another 6 beam samples is for 5% and 15% of rice husk replacement respectively. The results from this study indicates that, the ultimate loading capacity between 5% raw rice husk replacement beam and controlled beam show no huge differences. However, the ultimate loading capacity decrease when the rice husk replacement increase up to 15%. In addition, the deflection of 5% testing sample and controlled beam sample shows positive outcome where both deflection value is quite same. For the 15% sample, the curve of deflection shows that the deflection occurs faster than other two samples. The maximum moment also keep decreasing when the 15% replacement of rice husk in the beam while no big gap between the controlled beam and 5% beam samples. The aim of this experimental study is to contribute the idea to construction industry in order to produce economical buildings with same quality of strength, help in saving the natural sources and also help the government on the issues of constraint landfill area. All the testing is conducted in laboratory by the competent technical staff and the result is gathered and analyse precisely.